Grinding assessment of workpieces with different interrupted geometries using aluminum oxide wheel with vitrified bond - Fonteque Ribeiro, Fernando Sabino [UNESP]; Lopes, Jose Claudio [UNESP]; Garcia, Mateus Vinicius [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Mello, Hamilton Jose de [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
Among conventional machining processes, grinding presents itself as a material removal process that can produce workpiece with excellent surface finish and high geometric precision. Given the high industrial demand, more and more machining methods are being sought to allow high production speeds coupled with reduced costs. The requirement for high productivity and low-cost grinding processes often bumps into the geometry of the desired workpiece. Numerous grounded components in the automotive, aeronautics, and naval industries have geometric interruptions, such as ring seating channels and lubrication ducts. Interrupted grinding leads to shorter tool life and can lead to a decrease in the dimensional and surface quality of the mechanical component, thus requiring grinding of these components at low speeds. Thus, the present paper shows an experimental evaluation of interrupted cylindrical grinding of hardened steel AISI 4340 with vitrified aluminum oxide grinding wheel. Interrupted circular workpieces (2, 6, and 12 channels) were applied to simulate interruptions found in mechanical components subjected to interrupted grinding at feed rates of 0.25, 0.50, and 0.75 mm/min, at cutting speed of 32 m/s, under conventional lubrication, compared with uninterrupted workpieces under the same machining conditions. The output parameters evaluated were surface roughness, roundness deviation, grinding power, micrography, diametral wheel wear, and G-ratio, being evaluated statically by analysis of variance (ANOVA). There were no verified regions with burning or microcracks in all conditions. Still, the increase in the rate of advancement generated a drop of up to 68.7% in surface roughness, 40.5% in shape errors, and an increase in diametrical degreasing of the average grinding wheel of 90.9%. The wheel wear was more accentuated due to the number of interruptions, reaching a wear rate of up to 252% higher than the conventional condition.
Keywords: Hardened steel AISI 4340; External cylindrical grinding; Interrupted grinding; Vitrified aluminum oxide grinding wheel